Design estratégico para sustentabilidade na moda: um estudo de caso múltiplo - Araujo, Roberto Zimmer (Universidade do Vale do Rio dos Sinos, 2017)
This research aims to describe ways of contributing of strategic design to development of a culture of sustainability through projecting business in the fashion segment. Strategic design is understood as a knowledge area that consider the designer in all process of the strategy of the organization and generates a diversity of devices types, including business models, and consider the ecosystemic relations that are stablished. The fashion segment is a sector in which there are initiatives to design business models with sustainable purpose, and from ecosystemic relations the phenomenon of values related to its vision of sustainability. To understand how fashion business contribute to the construction of a sustainable culture through the design of business models there were studied three social business cases: Revoada, Colibrii and Tiê Moda Sustentável. The study is of a qualitative nature and is based on a constructivist-interpretative paradigm. The action plan consists in depth interviews and documental research, and content analysis. As results, it was perceived this business are creates from entrepreneurs identified with sustainability in personal live, and when they design the business perceived the possibility to practice and disseminate this perspective. With this, it’s perceived the influence of designer to transition toward sustainability from projects that stimulate more sustainable lifestyles and cultural transformation. The designer express on the business model that projects elements of its subjectivity in the form of social relations and with the environment not just in the business itself, but too all the supply and operative chain to do the impact intended. In the relations established with other actors in the business model the sustainable values are disseminated in material and immaterial exchanges, evolving the conscience of all connected actors. The business models should be understood as an open system for recreating process of themselves in consequence of the evolution of the conscience from the ecosystemic relations.
Keywords: Design estratégico; Sustentabilidade; Moda; Relações ecossistêmicas; Negócios sociais; Strategic design; Sustainability; Ecosystemic relations; Social business; Fashion; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial